Changes in serum lipid profile of castrated dogs - M. N. A. Rocha (Scientific Electronic Archives, 2016)
The present study was to evaluate possible changes in serum lipid profile of castrated dogs, weight gain, body fat percentage and IMCC, and possible correlations of these changes with the time of castration. We also evaluated the influence of variations of sex, age, size, type of nutrition and physical inactivity on the serum levels of cholesterol, triglycerides and glucose, weight gain, percentage of body fat and IMCC. We evaluated 44 dogs, seven entire and 37 castrated, without distinction of race and gender, aged one to 13 years, healthy. The dogs were divided into six groups according to the length of castration and a control group. Morphometric measurements were used to calculate the percentage of body fat, and IMCC calculation was also performed. In addition, animals were weighed and sorted in body condition scores. Serum levels of cholesterol, triglycerides, and glucose were measured for verification of probable alteration. Regarding the results, there was influence of sex and size (P≤0,05) on cholesterol levels, the size also influenced (P≤0,05) the percentage of body fat and the IMCC. Age influenced (P≤0,05), triglyceride levels. The type of feeding had effect (P≤0,05) in the IMCC and physical inactivity affected (P≤0,05) the percentage of body fat. It was also verified that there is correlation between time since castration and serum cholesterol, triglycerides and glucose, as well as weight gain, fat percentage and IMCC.